A survey of zoonotic pathogens carried by house mouse and black rat populations in Yucatan, Mexico - Panti-May, Jesus Alonso (2017)
Consejo Nacional de Ciencia y Tecnología (grant numbers 2014-247005 and 2008-108929), the National Institutes of Health (R01 TW009504) and the Wellcome Trust (102330/Z/13/Z).